Variation characteristics of stress distribution in the subchondral bone of the knee joint of judo athletes with long-term stress changes - Li, Zhiqiang; Xu, Guanghua; Wang, Chengjun; Wang, Qiuyuan; Liu, Caiping; Guo, Tingting; Wu, Lijun; Cao, Diankang (Frontiers in Endocrinology, 2023)
To investigate the distribution of BMD in the subchondral bone tissue of the knee joint due to the mechanical stress load generated by judo, the volume share of bone tissue of different densities and the bone remodeling characteristics of the subchondral bone of the knee joint. Knee CT imaging data were collected from 15 healthy individuals as controls and 15 elite judo athletes. First, it was processed by CTOAM technology, and secondly, high-density zones of knee joint were localized using nine anatomical regions. In addition, three tomographic images were selected in the 2-dimensional image window to observe the distribution of bone tissue with different densities. Finally, the percentage volume and bone remodeling trend and stress zones of different densities of bone tissue were determined. In this study, high-density areas were found in the intercondylar fossa of the distal femoral articular surface of judo athletes and in the medial and lateral regions of the tibial plateau; the subchondral bone in the distal femur and tibial plateau in judo athletes was low (partial), moderate, and high in the subchondral bone. The percentage of density (BMD) %BTV was higher than that of the control group (P < 0.05).The history of compressive stresses, struck stresses, soft tissue tension and pull, self-gravity and intra-articular stress loading generated by the lower limb exercise technique of judo leads to specific forms of stress distribution and bone tissue remodeling in the subchondral bone tissue within the distal femur and tibia plateau.